2020
DOI: 10.18203/2320-1770.ijrcog20203299
|View full text |Cite
|
Sign up to set email alerts
|

Postdated pregnancy: its maternal and fetal outcome

Abstract: Background: Postdated pregnancy is one of the commonest obstetric conditions. Pregnancy is called term when it lies between 37 weeks to 42 weeks from the last menstrual period. If the pregnancy exceeds 40 weeks it is called as postdated pregnancy. The overall incidence of post term pregnancy is 7% of all pregnancies.Methods: This observational study was carried out in the department of obstetrics and gynecology in Dr Ram Manohar Lohia Institute of Medical Sciences, Lucknow, Uttar Pradesh, India from September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 10 publications
5
14
1
Order By: Relevance
“…21 Singh N et al in 100 post dated deliveries studied that c-section and instrumental delivery was performed in 32% and 2 % respectively. 22 Our study showed even higher rate of LSCS of 40.13 % and 2 % of instrumental delivery. Fetal distress with meconium-stained liquor was observed as the most common indications for caesarean Section (36.06%) followed by oligohydramnios (29.22%) and failed induction (21.31%).…”
Section: Resultssupporting
confidence: 42%
“…21 Singh N et al in 100 post dated deliveries studied that c-section and instrumental delivery was performed in 32% and 2 % respectively. 22 Our study showed even higher rate of LSCS of 40.13 % and 2 % of instrumental delivery. Fetal distress with meconium-stained liquor was observed as the most common indications for caesarean Section (36.06%) followed by oligohydramnios (29.22%) and failed induction (21.31%).…”
Section: Resultssupporting
confidence: 42%
“…Similarly, a study done in Lucknow, India also showed that the maximum (81%) was in 40 weeks to 41 weeks of gestation. 3 Another study done in Nagpur, India showed that majority of the mothers (69.8%) were also in 40 -41 weeks of gestation. 8 In contrast to the study's finding, a study conducted in Ahemdabad, India, revealed that more than half of the mothers 54.76 % were more than 41 weeks of gestation.…”
Section: Discussionmentioning
confidence: 97%
“…8 In the present study, indications for caesarean section was fetal distress in 53.3% mothers, non-progress of labor in 13.3 % cases, cephalopelvic disproportion in 10% cases, severe oligohydramnios in 11.6% cases and failure of induction in 11.6% mothers.The indications of caesarean section in the study is similar with a study done in Dr. Ram Manohar Lohia Institute of Medical Sciences, Lucknow, where indication for caesarean section was meconium stained liquor with fetal distress in (26%) cases, failure of induction in (21%) cases , cephalo-pelvic disproportion in (16%) cases, severe oligohydramnios in (19%) and nonprogress of labor in (15%) cases. 3 Another study done in Jammu resulted that indication for caesarean section was failure of induction in 33.3% cases, fetal distress in 19.3% cases, non-progress of labor in 14.2% of cases cephalopelvic disproportion in 9.5% cases. 10 Nearly similar findings were noted in a study done in Wardha India which showed that the indication for caesarean section were fetal distress in 23.53% cases, failure of induction in 20.59% cases, cephalopelvic disproportion in 17.65% cases, non-progress of labor in 14.71% of cases.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations